Injection of liquid swine slurry and effects on properties of a Nitossolo Vermelho - Rech C.* (2018)
© 2018 Embrapa.The objective of this work was to evaluate the superficial and injected applications of swine slurry and urea to the soil, regarding their effects on the physical properties of a Nitossolo Vermelho distroférrico under a no-tillage system. The treatments were: injected slurry into the groove with a liquid swine slurry injector (LSSI); slurry on surface, applied on the lines by the LSSI kept raised; urea injected by opening the groove with the LSSI and distributed manually; and corn, under no-tillage, as a control. Sowing and the injection of liquid slurry or urea do not modify the organic carbon content, pH, and aggregation, but alter the soil bulk density and porosity in the mobilized line, and increase the macropores.